Engineering of Junior High School New Student Admissions System Using System Performance Based Prototype Method - Darsanto (NUANSA INFORMATIKA, 2025)
The process of accepting new students in Junior High Schools (SMP) is currently still constrained by a conventional system that requires physical collection of registration forms, complete files, and time-consuming interviews and tests. Information related to admission procedures, requirements, fees, and registration schedules is also spread across various communication channels, making it difficult for prospective students and parents to access accurate and up-to-date information. In this context, researchers have succeeded in designing a new student admission information system by implementing the prototype method. This system has gone through Black Box Testing and evaluation with the System Usability Scale (SUS) scale, and its performance has been analyzed using the Performance, Information, Economy, Control, Efficiency, Services (PIECES) method. The results of the SUS scale calculation show an average value of 72.9, which is included in the acceptable classification indicating that the New Student Admissions (PPDB) system in the form of a prototype after evaluation can be accepted by prospective users of the prototype system. In addition, the results of the PIECES calculation show that each indicator in the evaluation and measurement of the new student admissions system is in the "very good" and "good" categories , with an average value of 6.22 to 6.56 included in the very good category, an average value of 6.09 is included in the good category